2021
DOI: 10.12968/bjon.2021.30.12.734
|View full text |Cite
|
Sign up to set email alerts
|

Redeployment during the first wave of the COVID-19 pandemic: implications for a clinical research workforce

Abstract: Background: Health professionals are considered a group vulnerable to developing mental health symptoms during a pandemic, with redeployment being a risk factor. However, previous literature suggests workplace communication can be a protective element. Aims: An audit aimed to evaluate NHS research staff's experiences of redeployment in order to provide suggestions for future improvements in the process. Methods: A questionnaire was disseminated to all staff in the clinical research directorate of an NHS trust.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Our results regarding nurses' response to redeployment are consistent with previous studies among medical doctors [1], clinical research staff [15] and specialist nurses [16,17], who reported increased levels of self-reported stress and anxiety. While this psychological response may have been caused by the fear of contracting COVID-19, other factors need to be considered.…”
Section: Discussionsupporting
confidence: 91%
“…Our results regarding nurses' response to redeployment are consistent with previous studies among medical doctors [1], clinical research staff [15] and specialist nurses [16,17], who reported increased levels of self-reported stress and anxiety. While this psychological response may have been caused by the fear of contracting COVID-19, other factors need to be considered.…”
Section: Discussionsupporting
confidence: 91%
“…We are yet to see the full consequences of redeployment but there is an early suggestion of associated negative psychological effects. 18 The GIRFT report highlighted the importance of staff retention, particularly in addressing nursing turnover rates. 10 We identified that the band 5 vacancy rate increased from 13.5% in 2019 to 16.5% in 2021 suggesting a deteriorating position.…”
Section: Discussionmentioning
confidence: 99%
“…Mean sickness rate was 8%, compared with 2.6% in 2019, with no clear variation between sectors or regions. We are yet to see the full consequences of redeployment but there is an early suggestion of associated negative psychological effects 18. The GIRFT report highlighted the importance of staff retention, particularly in addressing nursing turnover rates 10.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants had limited awareness of what available support services were for and how to access them; related research has found that clear communication was important in determining MHW outcomes amongst redeployed staff surveyed in one Trust (Walker & Gerakios, 2021). Our findings highlight the difficulties of defining ‘clear communication’, with many staff unaware of services that Trust administrative and communications teams presumably believe to be advertised clearly.…”
Section: Discussionmentioning
confidence: 99%